2008
DOI: 10.1002/hed.20795
|View full text |Cite
|
Sign up to set email alerts
|

Speech Handicap Index in patients with oral and pharyngeal cancer: Better understanding of patients' complaints

Abstract: Results of this initial psychometric study indicate that the SHI is a reliable and valid questionnaire for assessing speech problems. Additional research is needed to evaluate responsiveness of the questionnaire to changes in speech-related problems over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 37 publications
3
97
1
3
Order By: Relevance
“…The English language version of SHI has shown high values of reliability and validity scores that are parallel to the Dutch version, 2 indicating it to be a good tool for evaluating the impact of speech impairment in patients with head and neck cancer. Patients can easily complete it while waiting for their turn to come in the outpatient department.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The English language version of SHI has shown high values of reliability and validity scores that are parallel to the Dutch version, 2 indicating it to be a good tool for evaluating the impact of speech impairment in patients with head and neck cancer. Patients can easily complete it while waiting for their turn to come in the outpatient department.…”
Section: Discussionmentioning
confidence: 98%
“…The development of the Dutch version of the SHI was largely based on the widely used and popular voice-specific scale the ''Voice Handicap Index'' (VHI) 32 by Rinkel et al 2 Consequently, our English version of SHI (Appendix) is on the same lines. 32 It has 30 well-constructed questions to evaluate the patient's speech and psychosocial functions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Lazarus et al (2014) noted that HNC survivors' reported impaired speech, as measured by the Speech Handicap Index (Rinkel, Verdonck-de Leeuw, van Reij, Aaronson, & Leemans, 2008), following chemoradiotherapy. This was in contrast to clinicianperceptions of complete intelligibility, both before chemoradiotherapy treatment, and at 3 and 6 months post-treatment.…”
Section: Introductionmentioning
confidence: 99%